Response to ‘Response to Doctors for Life on Assisted Suicide’ - A Van Eeden; S Nemutandani; M Meiring; L L Honey; H (WJ) Steinberg; T Hardcastle; M Bac; J V Larsen; K Michael; M Louw; W Sieling (South African Medical Journal)
-